A new CO2 laser technique for the treatment of pediatric hypertrophic burn scars: An observational study. Issue 42 (October 2016) - Żądkowski, Tomasz; Nachulewicz, Paweł; Mazgaj, Maciej; Woźniak, Magdalena; Cielecki, Czesław; Wieczorek, Andrzej Paweł; Beń-Skowronek, Iwona
Abstract : Abstract: Treatment of hypertrophic scars arising as a result of thermal burns in children is still a big problem. The results of the treatment are not satisfactory for patients and parents, and new methods of treatment are still investigated. We present the use of one of the most modern carbon dioxide (CO2 ) lasers (Lumenis Encore laser equipped with a Synergistic Coagulation and Ablation for Advanced Resurfacing module) in the treatment of hypertrophic scars in children after burns. From March to April of 2013, a group of 47 patients aged 6 to 16 years underwent 57 laser surgery treatments. The average time from accident was 7.5 years. The results of treatment were investigated in 114 areas. The assessed areas were divided into 2 groups: 9-cm 2 area 1, where the thickness of the scar measured by physician was the lowest and 9-cm 2 area 2, where the thickness of the scar was the biggest. The results were considered on the Vancouver Scar Scale (VSS) independently by the surgeon and by parents 1, 4, and 8 months after the procedure. In addition, ultrasound evaluation of the scar thickness before and after laser procedure was made. VSS total score improved in all areas assessed by both the physician and parents. The biggest change in total VSS score in area 1 in the evaluation of the investigator was obtained at follow-up after the 1st month of treatment (average 7.23 points before and 5.18 points after the 1st month after surgery—a difference of 2.05 points). Scar ratings by parents and the physician did not differ statistically ( P  < 0.05). In the ultrasound assessment, the improvement was statistically significant, more frequently for both minimum and maximum thickness of the scars (B-mode measures) ( P  < 0.05). The use of a CO2 laser in the treatment of hypertrophic scars in children is an effective and safe method. The use of a CO2 laser improves the appearance and morphology of scarring assessed using the VSS by both the parents and the physician. The treatment also reduced the thickness of scars evaluated by ultrasound.